Numerical Investigation of Oil Shale in Asphalt for Road Surfacing Using COMSOL Multiphysics - Alouani, Mohamed-Amine; Saifaoui, Dennoun; Boulezhar, Abdelkader; Lakrad, Faouzi; Alouani, Mouaad (Salehan Institute of Higher Education, 2026)
This study introduces a sustainable, performance-driven approach to asphalt pavement design by incorporating oil shale-modified bitumen into hot-mix asphalt (HMA) and evaluating four performance grade (PG) binders. The research provides a comprehensive evaluation of mechanical and rheological behaviors across varying thermal and loading conditions. A key innovation lies in the integration of oil shale, which significantly reduces voids in mineral aggregates (VMA), leading to improved aggregate contact and material densification. This microstructural enhancement directly translates into increased dynamic modulus (E*) and shear modulus (G*), reinforcing the mixture’s stiffness and deformation resistance without the need for costly chemical additives. The results demonstrate that oil shale improves the load-bearing capacity of asphalt mixtures, particularly under high-frequency loading where elastic responses are favored. Moreover, the optimized mixtures maintain a favorable balance between rigidity and flexibility, typically prone to compressive deformation, and benefit from oil shale integration through enhanced stress dissipation characteristics. The study offers a novel pathway for valorizing oil shale, a locally abundant, underutilized material, as a functional asphalt modifier. The findings validate its potential to extend pavement service life, optimize stiffness–temperature profiles, and reduce dependency on virgin bitumen. These results position oil shale as a viable, cost-effective, and environmentally advantageous additive for future-proof pavement engineering.